(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the implementation of Early Warning Score (EWS) in hospitals. The method used is a case report including assessment, problem identification, problem analysis using fishbone, preparation of plan of action (PoA), implementation and evaluation. Data collection was carried out using interviews and field observations. The results showed that the hospital had implemented a system to prevent worsening to patients using a tool called Early Warning Score (EWS), but the application of EWS was still not optimal. The problem was solved using Kurt Lewin’s planned change approach with the implementation carried out by making training, case discussions, quizzes and monitoring and evaluating the implementation of EWS in the hospital. In conclusion, increasing competence by providing training, discussions about EWS and conducting monitoring and evaluation can optimize the implementation of EWS in hospitals. Keywords: Nurse, Patient Safety, Early Warning System, Implementation